O Chapadão do Diamante na Serra da Canastra/MG, Brasil: caracterização geomorfológica e análise integrada do meio físico a partir de dados multifontes - Nazar, Thallita Isabela Silva Martins (2018)
The Chapadão do Diamante (ChD) is the summit area of Serra da Canastra, in its eastern portion, located in the Southwest Region of Minas Gerais, Brazil. The area is part of the Serra da Canastra National Park, and is structured by a packet of pure and micaceous quartzites with phyllites, from the Canastra Indeterminate Group, which conditions a distinct landscape with different relief patterns. The geomorphological dynamics associated with the lithostructural aspects and surface materials was the main focus of the thesis, complementing the knowledge gap in the literature in this regard. Thus, we attempted to carry out the cartographic survey and the spatial analysis of the ChD, based on multifonts data, in order to interpret the physical environment and geomorphological dynamics. Therefore, several methods and techniques were applied in Geographic Information Systems environment with the use of Digital Terrain Models (TDM); and also, in the field and laboratory, with collect of surface materials samples and physical and mineralogical analysis of samples. From the point of view of the relief, from semi-automated analyzes of geomorphometric parameters based on the lithological base and in situ observations, it was possible to affirm that the ChD includes flattened reliefs; dissected reliefs; elongated crests with quartzitic outcrops, and at its edges, escarpment relief with free faces. This morphological configuration presents strong interdependence to the lithostructural aspects and to the geo-covers, which were mapped from Google ™ images, aerogamaespectrometric data and field observations. The results of this survey indicated a variation of the characteristics of the materials in function of topographic aspects; presence of radioelements such as Th and K; and structural discontinuities. In addition, analyzes of zonal statistics in the spatial analysis approach allowed the evaluation of the surface formations data in relation to the relief classes and land-surfaces parameters, such as slope and curvature. The statistical tests showed an interdependence between the mentioned aspects, allowing to understand the ChD as a complex landscape, where there is an important relationship between the lithostructural, geomorphological and surface elements. Finally, laboratory analyzes were performed according to three sample transects, selected in different environments. The results showed the presence of clay and oxides / hydroxides of Fe and Al, due to the deep weathering of the rocks, with indications that these processes have been operating for a long time in tropical climate conditions, even taking into account the resistance of quartzite rocks. In summary, this thesis presents an unprecedented approach to the Chapadão do Diamante, recognizing important landscape aspects, with the expectation that it will serve as a basis for the continuity of research in the area.